2016
DOI: 10.1016/j.rbr.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de ansiedade, depressão e cinesiofobia em pacientes com lombalgia e sua associação com os sintomas da lombalgia

Abstract: There was no association between the groups and anxiety and depression. However, there was a positive correlation between kinesiophobia and the Organic group. Studies of other patient samples are needed to confirm the reproducibility and validity of these data in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Studies in both Spain and the Netherlands have found that CBP was significantly associated with a higher risk of depression and a significantly higher risk of developing a later mood disorder, respectively [ 8 , 13 ]. Notwithstanding the significant amount of research globally, public health officials in Brazil had no generalizable studies that showed a link between self-reported CBP and SRCD, as previous research had been on a small scale and contradictory [ 24 , 25 ]. Using the results of this current study, they will be able to demonstrate the significant association between self-reported CBP and SRCD in order to guide policy change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in both Spain and the Netherlands have found that CBP was significantly associated with a higher risk of depression and a significantly higher risk of developing a later mood disorder, respectively [ 8 , 13 ]. Notwithstanding the significant amount of research globally, public health officials in Brazil had no generalizable studies that showed a link between self-reported CBP and SRCD, as previous research had been on a small scale and contradictory [ 24 , 25 ]. Using the results of this current study, they will be able to demonstrate the significant association between self-reported CBP and SRCD in order to guide policy change.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has only been studied previously in Brazil on a very limited scale and with contradicting results. Trocoli and Botelho found no association between CBP and depression among 65 patients who presented to a walk-in clinic with back pain in São Paulo, Brazil in 2015 [ 24 ], while Rodrigues de Souza et al, found a significant association between depression and CBP in 2016 among 30 patients with back pain in São Carlos, Brazil [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Tampa Kinesiophobia Scale defined as excessive, irrational and debilitating fear of movement, is commonly found in patients with fibromyalgia due to the association between pain/fatigue and movement increasing the patient’s disability 40 . The Tampa kinesiophobia scoring scale follows a specific dynamic of the sum of responses present in a questionnaire with seventeen questions, where the final values can vary from 17 to 68 points, with a mild classification (17 to 34 points), moderate (35 to 40 points) and severe (51 to 68 points) 41 .…”
Section: Methodsmentioning
confidence: 99%
“…The nal score can be at least 17 and a maximum of 68. The Kinesiophobia classi cation is divided into light (17 to 34 points), made up to (35 to 50 points) and serious (51 to 68 points) (22).…”
Section: Kinesiophobiamentioning
confidence: 99%